2020
DOI: 10.1007/s00267-020-01377-3
|View full text |Cite
|
Sign up to set email alerts
|

University Stormwater Management within Urban Environmental Regulatory Regimes: Barriers to Progressivity or Opportunities to Innovate?

Abstract: U.S. public university campuses are held directly responsible for compliance with many of the same federal-and state-level environmental regulations as cities, including stormwater management. While operating as 'cities within cities' in many respects, campuses face unique constraints in achieving stormwater regulatory compliance. To compare the abilities of campuses to comply with stormwater regulations to municipalities, we conduct mixed-methods research using primary data from five University of California … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Put simply: the mechanisms for placing an economic value on GSI's benefits remain under‐developed. As a result, many jurisdictions struggle to identify funding streams necessary for GSI development and maintenance, even in contexts where there is widespread support for the adoption of such infrastructures (Pierce et al, 2021). Notably, this characterization holds true within China's much‐lauded Sponge Cities, which have had difficulty obtaining financial support for sustained GSI maintenance (L. Li et al, 2020; Qiao et al, 2019).…”
Section: Reviewed Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Put simply: the mechanisms for placing an economic value on GSI's benefits remain under‐developed. As a result, many jurisdictions struggle to identify funding streams necessary for GSI development and maintenance, even in contexts where there is widespread support for the adoption of such infrastructures (Pierce et al, 2021). Notably, this characterization holds true within China's much‐lauded Sponge Cities, which have had difficulty obtaining financial support for sustained GSI maintenance (L. Li et al, 2020; Qiao et al, 2019).…”
Section: Reviewed Barriersmentioning
confidence: 99%
“…Most commonly suggested solutions to overcome the institutional barriers are related to more effective coordination, communication, collaboration, and cooperation between the teams involved in the GSI projects (Drosou et al, 2019; Gashu & Gebre‐Egziabher, 2019; C. Li et al, 2019; Onori et al, 2019; Pierce et al, 2021; Shafique & Kim, 2017). Departmental policy integration (Drosou et al, 2019) and improved partnership among stakeholders (Angelstam et al, 2017; Sarabi et al, 2019) to overcome institutional fragmentation are among other cited solutions.…”
Section: Reviewed Solutionsmentioning
confidence: 99%
“…Three of the five campuses in our sample have disproportionately large populations or land areas compared to their surrounding municipalities and three contain or discharge runoff to environmentally sensitive, protected habitat (UC Santa Barbara 2014; UC Irvine 2018; UC San Diego 2019). Our previous research found that, like municipal Public Works Departments, campus Environmental Health and Safety (EHS) offices shoulder the burden of responsibility for urban runoff compliance (Pierce et al 2020). Campuses can serve as pilot areas for innovative green infrastructure approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for innovative water supply solutions, universities can serve as living laboratories for new ideas that require evaluation and field-testing before they are implemented on a city- or state-wide scale . In that spirit, the five University of California campuses in Southern California participated in a multi-year research project, “Fighting Drought with Stormwater,” focused on identifying and overcoming perceptual, regulatory, and technical barriers associated with making stormwater a significant component of Southern California’s water supply portfolio. , Focusing on the University of California, Irvine (UCI) campus in Irvine, California, as a test bed, this paper answers the following question: what are the best-case limits of an RTC stormwater capture system on the UCI campus relative to delivering water supply and stormwater retention benefits, and how do these benefits depend on the total rainfall each year and the region’s seasonal patterns of precipitation?…”
Section: Introductionmentioning
confidence: 99%